Advertising and how it is affected by culture when to use a standardized versus customized approach - Isaacs, Cory (My University, 2007)
This paper is a study of the international marketing strategies of standardization and customization relating to national cultures. The test countries are Canada and Finland. The main aim of this study is to discover which strategy is best suited for advertising in international markets. Canada and Finland are two countries that share many similarities, both geographical and cultural. Therefore, this study takes a unique approach by comparing similar countries to look for differences as opposed to the majority of studies that use countries that are culturally dissimilar. This paper studies cultural aspects and cultural research then moves into international advertising and the debate between standardization and customization of international advertisements. An interview and advertisement analyses was used to carry out the exploratory research to complete the empirical part. The decision to standardize or customize an international campaign is often decided upon using perceived economies of scale. Cost savings in this area often lead to lost sales and therefore are more than negated. Modern research has shown that as nations become richer and individuals earn more they actually actively seek out to differentiate themselves and their culture from a global culture. The findings of this paper provide insights into international advertising between countries that are similar and share some of the same cultural traits. The end of the research paper leads to managerial implications of international marketing and areas of future research because international marketing is perceived to be underdeveloped. The research shows that even if agreement on terms cannot be found, countries with similar cultures can use similar advertisements with slight modifications when needed.
Keywords: international advertising; culture; standardization; customization; fi=Markkinointi|en=Marketing|